PENINGKATAN KAPASITAS RELAWAN DALAM MENGHADAPI BENCANA DI DESA TEMBOKREJO KECAMATAN MUNCAR KABUPATEN BANYUWANGI - Kurniawan, Ficky Adi; Effendi, Effantra; Prasetyo, Anggoro Budi (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2023)
Tembokrejo Village is one of the villages in Muncar District which has the densest population. The location of Tembokrejo Village is directly adjacent to the Bali Strait which has the potential for a tsunami disaster. With such a large population, the level of risk from a tsunami disaster is very high. Since 2021 in Tembokrejo Village a Disaster Risk Reduction Forum and Volunteers have been formed in the Village. However, over time there have been changes in members. So it is necessary to increase the capacity and knowledge of new volunteers and remind the old members. The method used is qualitative descriptive. The results obtained are many volunteers who still do not have a full volunteer spirit. This can be seen from the activeness and participation of members when handling disaster events in Tembokrejo Village. For this reason, it is necessary to continue to foster a spirit of volunteerism and knowledge from members, who will later become the frontline in disaster management in Tembokrejo Village)